2022
DOI: 10.3390/vetsci9090475
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils as a Dietary Additive for Small Ruminants: A Meta-Analysis on Performance, Rumen Parameters, Serum Metabolites, and Product Quality

Abstract: There is an increasing pressure to identify natural feed additives that improve the productivity and health of livestock, without affecting the quality of derived products. The objective of this study was to evaluate the effects of dietary supplementation with essential oils (EOs) on productive performance, rumen parameters, serum metabolites, and quality of products (meat and milk) derived from small ruminants by means of a meta-analysis. Seventy-four peer-reviewed publications were included in the data set. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 164 publications
2
19
0
Order By: Relevance
“…Secondly, the articles analyzed had to meet some previously defined inclusion criteria to be included in the final database. In the present meta-analysis, the inclusion criteria used were similar to those previously reported by Dorantes-Iturbide et al ( 35 ) and Orzuna-Orzuna et al ( 36 ): (1) studies with beef cattle or dairy cows housed in confined conditions; (2) data on animal performance, nutrient digestibility, antioxidant status in blood serum, carcass characteristics, ruminal fermentation or quality of the derived products (meat or milk); (3) studies that had control and experimental treatments with similar diets, except for the presence of FLAs in the diets; (4) studies that reported the doses of FLAs used or had sufficient information to estimate the amount of FLAs included in the diets; (5) studies written and published in English and in peer-reviewed scientific journals; and (6) studies that reported the means of the control and FLA-supplemented treatments, the standard error or standard deviation, and the number of replicates.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…Secondly, the articles analyzed had to meet some previously defined inclusion criteria to be included in the final database. In the present meta-analysis, the inclusion criteria used were similar to those previously reported by Dorantes-Iturbide et al ( 35 ) and Orzuna-Orzuna et al ( 36 ): (1) studies with beef cattle or dairy cows housed in confined conditions; (2) data on animal performance, nutrient digestibility, antioxidant status in blood serum, carcass characteristics, ruminal fermentation or quality of the derived products (meat or milk); (3) studies that had control and experimental treatments with similar diets, except for the presence of FLAs in the diets; (4) studies that reported the doses of FLAs used or had sufficient information to estimate the amount of FLAs included in the diets; (5) studies written and published in English and in peer-reviewed scientific journals; and (6) studies that reported the means of the control and FLA-supplemented treatments, the standard error or standard deviation, and the number of replicates.…”
Section: Methodsmentioning
confidence: 97%
“…After applying the inclusion criteria, only 36 peer-reviewed articles were included in the final database ( Supplementary Table S1 ). Likewise, we only extracted quantitative data for response variables that were reported in at least three individual studies ( 31 , 35 , 36 ). Among the response variables included in the final database of this meta-analysis are the following: dry matter intake and nutrient digestibility (neutral detergent fiber, crude protein), daily weight gain, feed conversion ratio, carcass characteristics (carcass yield, backfat thickness), serum concentration of malondialdehyde and antioxidant enzymes (for example, superoxide dismutase), serum immunoglobulins (IgA, IgM, and IgG), rumen parameters (pH, ammonia nitrogen), physicochemical characteristics of the meat (pH, shear force, color), milk production, and milk composition (lactose, protein, and fat content).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that the effects of EOs on ruminal nitrogen metabolism are mediated by their effect on hyper-ammonia producing bacteria, leading to a decrease in amino acid chemical alterations and ammonia nitrogen synthesis. There is conflicting evidence regarding the effects on methane generation, however, current data suggests that it is possible to select EOs or other handactive components that selectively inhibit ruminal methanogenesis (Benchaar et al 2008;Dorantes-Iturbide et al 2022). There is currently no evidence that aromatic plant EOs have antibacterial activity in ruminants in vivo.…”
Section: Dietary Ruminal Effects Of Essential Oilsmentioning
confidence: 99%
“…Effects of essential oils or their components on rumen characteristicsCobellis et al 2016;Aziz et al 2018;Poudel et al 2019;Ku-Vera et al 2020;Dorantes-Iturbide et al 2022 …”
mentioning
confidence: 99%